The combinations of sulfur and molybdenum fertilizations improved antioxidant capacity of grazing Guizhou semi-fine wool sheep under copper and cadmium stress - Yuanfeng Li (Ecotoxicology and Environmental Safety, 2021)
Mineral development and metal smelting are the main sources of heavy metal pollution, and copper (Cu) and cadmium (Cd) are the most serious mineral elements in heavy metal pollution. Food chain is the main channel for Cu and Cd to enter human body. Excessive accumulation of Cu and Cd can lead to a variety of diseases and threaten human health. Therefore, it is urgent to repair Cu and Cd-contaminated soil. Previous several studies found that sulfur (S) and molybdenum (Mo) had the effect of alleviating the decrease of antioxidant capacity caused by heavy metal poisoning. To investigate the co-combinations of S and Mo fertilizations on antioxidant capacity of grazing Guizhou semi-fine wool sheep in Cu and Cd-contaminated meadow, and explore the control methods of co-pollutions of Cu and Cd in natural pastures, fertilizing and grazing experiments were carried out in the Wumeng Prairie in the northwest of Guizhou Province, Southwest China. 24 hm2 Cu and Cd-polluted meadows were fenced, and were randomly divided into four groups with 3 replications per group and 2 hm2 per replication. The tested groups included the control group (no fertilizer) and the three treatment groups, applied 40 kg S + 1 kg Mo, 80 kg S + 2 kg Mo, and 120 kg S + 3 kg Mo per hectare for group I, group II, and group III, respectively. 72 healthy Guizhou semi-fine wool sheep (one year old, 33.9 ± 1.2 kg) were randomly assigned to the tested pastures with 18 sheep per group. The grazing experiment lasted for 60 days. The results showed that the contents of Mn, Zn, Mo, and S in herbage in fertilized pastures were higher than that in the control group (P < 0.05). The content of Cu in herbage in fertilized pastures was lower than that in the control group (P < 0.05). The contents of Mn, Zn, Mo, and S in serum of grazing Guizhou semi-fine wool sheep were higher than that in the control group (P < 0.05). The content of Cu in serum of grazing Guizhou semi-fine wool sheep was lower than that in the control group (P < 0.05). The levels of blood Hb, RBC, and PCV, and the activities of serum SOD, GSH-Px, T-AOC, CAT, and Cp in group Ⅲ were higher than that in the control group, group Ⅰ, and group Ⅱ (P < 0.05). The MDA content of sheep in group Ⅲ was lower than that in the other treatment sheep (P < 0.05). In summary, the combinations of S and Mo fertilizers influenced the mineral contents in herbage and serum of grazing Guizhou semi-fine wool sheep. The combinations of 120 kg S + 3 kg Mo fertilizer reduced the toxicity and improved antioxidant capacity of grazing Guizhou semi-fine wool sheep in Cu and Cd-polluted grasslands.